2016
DOI: 10.1111/jar.12320
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing and Treating Social Anxiety in Autism Spectrum Disorder: A Focus Group Study with Multidisciplinary Professionals

Abstract: Future studies should establish how aspects of the care pathway can be improved for individuals with ASD and SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Significant relationships between ASD severity and the parental-rated Revised Child Anxiety and Depression Scale (24), the parental-rated K-SADS-PL (25) or clinician-rated anxiety symptoms with the MINI-plus (26) was described. Five studies in adults with ASD (26)(27)(28)(29)(30) unlighted associations between self-reported social anxiety on the Liebowitz Social Anxiety Scale LSAS and socio communicative impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Significant relationships between ASD severity and the parental-rated Revised Child Anxiety and Depression Scale (24), the parental-rated K-SADS-PL (25) or clinician-rated anxiety symptoms with the MINI-plus (26) was described. Five studies in adults with ASD (26)(27)(28)(29)(30) unlighted associations between self-reported social anxiety on the Liebowitz Social Anxiety Scale LSAS and socio communicative impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential barrier to obtaining high quality and appropriate mental health support is the lack of tailored care, as autistic people and their families recurrently report that services and treatment approaches are rarely adapted to their needs (15). Impediments to delivering appropriate support include lack of staff training and knowledge on how services could be adapted, and lack of evidence on best approaches (11,(17)(18)(19)(20). This scarcity of tailored approaches and lack of information about effective tailored care further highlights the need to identify strategies used to improve access, experiences of care and mental health outcomes for autistic people.…”
mentioning
confidence: 99%
“…Reaven et al, 2015; J. Reaven, Blakeley-Smith, Leuthe, Moody, & Hepburn, 2012; Sofronoff, Silva, & Beaumont, 2017; Solish et al, 2020; Swain, Murphy, Hassenfeldt, Lorenzi, & Scarpa, 2019; Wise et al, 2019), two papers compared different samples before and after implementation of a new care pathway (Cervantes et al, 2019; Kuriakose et al, 2018), seven were surveys (Cooper, Loades, & Russell, 2018; Fisher, van Diest, Leoni, & Spain, 2023; Ford et al, 2019; Hollocks et al, 2019; Jones, Gangadharan, Brigham, Smith, & Shankar Background, 2021; Pickard et al, 2020; Stadnick, Brookman-Frazee, Nguyen Williams, Cerda, & Akshoomoff, 2015), and two were qualitative (Petty, Bergenheim, Mahoney, & Chamberlain, 2021; Spain et al, 2017). There were multiple papers that were from the same trials (Cervantes et al, 2019; Keefer et al, 2017; Kuriakose et al, 2018; Pickard et al, 2020; J.…”
Section: Resultsmentioning
confidence: 99%